PENERAPAN PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DENGAN METODE PREVIEW, QUESTION, READ, REFLECT, RECITE, AND REVIEW (PQ4R) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ARITMETIKA SOSIAL KELAS VII B SMPN 2 SUKOWONO TAHUN PELAJARAN - Harini, Dyah Ayu; Setiawan, Toto Bara; Susanto, S (Department of Mathematics Education , University of Jember, 2012)
Abstract. Numbered Head Together (NHT) is a kind of cooperative learning which specially designed to prevent the dominance of a certain student in the learning process. In fact the PQ4R method is used to help students to remember what they have read of some steps, namely preview, question, read, reflect, recite, and review. The subject of the research is grade VII B students of SMPN 2 Sukowono. The data collection methods used in this research are test, observation, interview, and documentation. The result of this research showed the increase of students’ activities and achievement. Clasically the students’ achievement of the cycle I was 10,5% and in cycle II increased to 86,80%. The result of this research also received a good response from the teacher and students. It was proven with increase of the students’ activities and achievement. The application of NHT type of cooperative learning and PQ4R method can increase their activities and achievement. Key Words : NHT type of cooperative learning with PQ4R method, student activities, achievement